Environmental Functional Nanomaterials - Wang, Qiang; Zhong, Ziyi (De Gruyter STEM, 2019)
Environmental Functional Nanomaterials covers the molecular structure and properties of nanomaterials used to remove refractory pollutants from industrial wastewaters and the environment with high efficiency. Insights into the innovations in the production of these new nanomaterials are provided. This book is ideal for career starters and students of materials science, environmental science, and chemistry.